Bypassing the Closest Stroke Center for Thrombectomy Candidates: What Additional Delay to Thrombolysis Is Acceptable?. Issue 3 (March 2020) - Schlemm, Ludwig; Endres, Matthias; Nolte, Christian H.
Abstract : Background and Purpose—: Patients with acute ischemic stroke who have large vessel occlusion benefit from direct transport to a comprehensive stroke center (CSC) capable of endovascular therapy. To avoid harm for patients without large vessel occlusion from delayed access to intravenous thrombolysis (IVT), it has been suggested to only redirect patients with high likelihood of large vessel occlusion for whom the additional delay to intravenous thrombolysis (IVT) caused by transport to the CSC is below a certain threshold. However, which threshold achieves the greatest clinical benefit is unknown. Methods—: We used mathematical modeling to calculate additional-delay-to-IVT thresholds associated with the greatest reduction in disability-adjusted life years in abstracted 2-stroke center and multiple-stroke center scenarios. Model parameters were extracted from recent meta-analyses or large prospective cohort studies. Uncertainty was quantified in probabilistic and 2-way univariate sensitivity analyses. Results—: Assuming ideal treatment time performance metrics, transport to the nearest CSC was the preferred strategy irrespective of additional delay-to-IVT when the transfer time between primary stroke center and CSC was <40 minutes (95% credible interval: 25–66 minutes); otherwise, the optimal additional delay-to-IVT-threshold ranged from 28 to 139 minutes. In multiple-stroke center scenarios, optimal additional-delay-to-IVT thresholds were 30 to 54 minutes in urban and 49 to 141 minutes in rural settings; use of optimal thresholds as compared with a 15 minute-threshold saved 0 to 0.11 and 0 to 0.37 disability-adjusted life years per triage case, respectively. Assuming slower treatment times at primary stroke centers and CSCs yielded longer permissible additional delays. Conclusions—: Our results suggest that patients with acute ischemic stroke with suspected large vessel occlusion should be redirected to a CSC if the additional delay to IVT is <30 minutes in urban and 50 minutes in rural settings.